Psychometric Properties of a Russian Version of the Cognitive Flexibility Inventory (CFI-R) - Kurginyan, Sergey S.; Osavolyuk, Ekaterina Y. (Frontiers in Psychology, 2018)
The Cognitive Flexibility Inventory (CFI) is a brief self-report measure of the type of cognitive flexibility (CF) necessary to successfully challenge and restructure maladaptive beliefs with more balanced and adaptive thinking; it is particularly popular for use with English speakers. The CFI has recently been translated into five languages (Chinese, Japanese, Iranian, Turkish, and Russian), although estimates of reliability and validity of these translated versions are scarce. This study reports on the factor structure, internal consistency, reliability, and construct validity of the CFI. We adopted the CFI for a Russian-speaking population, using student sample of 445 first and second-year undergraduates (M = 18.59 years, SD = 1.19) and found that a two-factor model fitted the data well. However, the structure of the CFI was revised because of some modifications, which were made to the original English to match the Russian equivalents of items originally developed to assess the definite aspect of cognitive flexibility. The CFI-R showed good internal consistency and suitable 7-week test–retest reliability. The construct validity of the Russian version of the CFI was studied by computing correlations with other related measures of CF (Attributional Style Questionnaire), depressive symptoms (Beck Depression Inventory), coping (Ways of Coping (Revised), and rigidity (Tomsk Rigidity Questionnaire). Furthermore, to assess whether the construct validity were affected by psychopathology we examined results for non-clinical and clinical samples, using “known-groups” method. The clinical sample reported lower CF than did the non-clinical sample on the CFI-R’s total score and its subscales’ scores. Findings in the present study suggest that the psychometric properties of the Russian CFI are comparable to the English original, making it appropriate to research assessment of the type of CF in Russian speaking population.